ABUSE OF FORCE BY MEMBERS OF THE DALMAS IN HANDLING DEMONSTRATIONS - Davin Ardra; Hafid Zakariya; Suparwi (PT. Radja Intercontinental Publishing, 2026)
Demonstrations are a form of implementation of human rights guaranteed by the 1945 Constitution of the Republic of Indonesia and Law Number 9 of 1998 concerning Freedom of Expression in Public. In its implementation, the Indonesian National Police (POLRI), especially the Dalmas (Community Police), has an obligation to maintain security and order during demonstrations. However, in practice, there are still cases of abuse of force by Dalmas members that are carried out excessively and disproportionately against demonstration participants. This study aims to analyze the forms of abuse of force by Dalmas members in handling demonstrations, the causes of abuse of authority, and law enforcement efforts against police officers who commit violations. The results of the study indicate that repressive actions by Dalmas officers that exceed the limits of authority are contrary to the principles of legality, proportionality, necessity, and respect for human rights as specified in applicable laws and regulations. This abuse of force can be categorized as a violation of the law, a violation of discipline, and a violation of the Indonesian National Police's professional code of ethics. Therefore, stricter oversight, increased professionalism of officers, human rights education, and reform of the police's legal culture are needed to achieve humane and democratic law enforcement.